Effects of Lactobacillus fermentum CQPC04 on Lipid Reduction in C57BL/6J Mice - Yi, Ruokun; Tan, Fang; Zhou, Xianrong; Mu, Jianfei; Li, Lin; Du, Xiping; Yang, Zhennai; Zhao, Xin (Frontiers in Microbiology, 2020)
Probiotics are functional foods that can effectively regulate lipid metabolism and maintain body health. In this study, a strain of Lactobacillus fermentum CQPC04 (LF-CQPC04) isolated from traditional naturally fermented vegetables (Sichuan pickles) was studied, and its effects on lipid metabolism in mice, as well as its mechanism of action, were observed. The results of this experiment show that LF-CQPC04 can reduce the abnormal weight gain and abnormal visceral index of mice caused by a high-fat diet. LF-CQPC04 can decrease TG (triglycerides), TC (total cholesterol), LDL-c (low-density lipoprotein cholesterol), AST (aspartate transaminase), ALT (alanine aminotransferase) and AKP (alkaline phosphatase) levels and increase HDL-c (high-density lipoprotein cholesterol) levels in the serum of high-fat mice. LF-CQPC04 can also decrease the levels of inflammatory cytokines, such as IL-6 (interleukin-6), IL-1β (interleukin-1 beta), TNF-α (tumor necrosis factor alpha) and IFN-γ (interferon gamma), and increase IL-4 and IL-10 levels in the serum of high-fat mice. The results of RT-qPCR (real time quantitative polymerase chain reaction) and western blot experiments show that LF-CQPC04 can also down-regulate the expression of PPAR-γ (peroxisome proliferator-activated receptor gamma), C/EBP-α (CCAAT/enhances binding protein alpha) mRNA and protein in the liver tissue of high-fat mice, while up-regulating the expression of Cu/Zn-SOD (copper/zinc superoxide dismutase), Mn-SOD (manganese superoxide dismutase), CAT (catalase), CYP7A1 (cholesterol 7 alpha hydroxylase), PPAR-α (peroxisome proliferator-activated receptor alpha), CPT1 (carnitine palmitoyltransferase 1) and LPL (lipoprotein lipase). Moreover, LF-CQPC04 shows stronger effects in regulating lipid metabolism in mice than L-carnitine and commercial LB (Lactobacillus delbrueckii subsp. Bulgaricus) bacteria. LF-CQPC04 is beneficial for lipid metabolism in animals and has good probiotic potential.